THE INFLUENCE OF AI-GENERATED CONTENT ON AUDIENCE TRUST IN DIGITAL MEDIA: A STUDY OF UNIVERSITY INTERNATIONAL STUDENT IN INDONESIA (Al-Aasar, 2026)
The following questions are used to guide the research:Artificial Intelligence (AI) has revolutionized the world of digital media, especially the profusion of AI-generated content, including automated news articles, synthetic images, and chatboats (Dwivedi et al., 2023). The use of these tools has enhanced productivity and content generation, but it has raised questions about trust, credibility, and the reliability of information. Trust on digital media has become less so in an age where it's difficult to distinguish between what is man-made and what is AI-generated. This study aims to analyze the impact of AI-generated content on trust in digital media, particularly among internationally-studied students in Indonesia who are a digitally literate and culturally diverse community. This study aims to explore how exposure to generated content affects user's trust and credibility in digital information, and how exposure to generated content affects the user's engagement with the content. The research method used is quantitative research design which is a structured research survey administered to the international students in universities in Indonesia. Through statistical analysis, links between AI content consumption and trust and other mediating factors (e.g., perceived transparency and media literacy) are uncovered. The findings suggested that there will be diminishing audience trust with increasing exposure to the use of AI-generated content unless there is transparency and source disclosure. Besides that, it is expected that trust ability in evaluating will be strengthened through media literacy as moderator. The research highlights a number of key issues for AI providers, digital media companies and policy makers, such as the need for clarity when labeling AI tools and the need for greater digital literacy initiatives. In conclusion, this study sheds light on the evolving landscape of trust in today’s communication landscape driven by AI.